Whole exome sequencing identifies TRIOBP pathogenic variants as a cause of post-lingual bilateral moderate-to-severe sensorineural hearing loss - Agnieszka Pollak; Urszula Lechowicz; Victor Abel Murcia Pieńkowski; Piotr Stawiński; Joanna Kosińska; Henryk Skarżyński; Monika Ołdak; Rafał Płoski (BMC, 2017)
Abstract Background Implementation of whole exome sequencing has provided unique opportunity for a wide screening of causative variants in genetically heterogeneous diseases, including nonsyndromic hearing impairment. TRIOBP in the inner ear is responsible for proper structure and function of stereocilia and is necessary for sound transduction. Methods Whole exome sequencing followed by Sanger sequencing was conducted on patients derived from Polish hearing loss family. Results Based on whole exome analysis, we identified two TRIOBP pathogenic variants (c.802_805delCAGG, p.Gln268Leufs*610 and c.5014G>T, p.Gly1672*, the first of which was novel) causative of nonsyndromic, peri- to postlingual, moderate-to-severe hearing loss in three siblings from a Polish family. Typically, TRIOBP pathogenic variants lead to prelingual, severe-to-profound hearing loss, thus the onset and degree of hearing impairment in our patients represent a distinct phenotypic manifestation caused by TRIOBP variants. The pathogenic variant p.Gln268Leufs*610 disrupts the TRIOBP-4 and TRIOBP-5 isoforms (both expressed exclusively in the inner ear and retina) whereas the second pathogenic variant c.514G>T, p.Gly1672* affects only TRIOBP-5. Conclusions The onset and degree of hearing impairment, characteristic for our patients, represent a unique phenotypic manifestation caused by TRIOBP pathogenic variants. Although TRIOBP alterations are not a frequent cause of hearing impairment, this gene should be thoroughly analyzed especially in patients with a postlingual hearing loss. A delayed onset of hearing impairment due to TRIOBP pathogenic variants creates a potential therapeutic window for future targeted therapies.